Diphtheria in adult - A case report - Swarna, S R; Sivagurunathan, Stalin; Bharathi, T; Kumar, Mohan; Lavanya, M; Jeyakumari, D (Indian Journal of Case Reports, 2020)
Diphtheria caused by Corynebacterium diphtheriae is a toxin-mediated upper respiratory tract infection. It spreads by airborne respiratory droplets and commonly affects children. The implementation of a Universal Immunization Program has resulted in a decline in the incidence. In spite of the ongoing immunization program, there is an intermittent re-emergence of diphtheria in developing countries like India. The resurgence of diphtheria in the recent past, with a shift in the age from children to adults, poses a major concern. Hereby, we report a case of isolation of toxigenic C. diphtheriae from an adult patient who suffered from diphtheritic tonsillitis.